Microglia shape corpus callosum axon tract fasciculation: functional impact of prenatal inflammation. (5th March 2014) - Pont‐Lezica, Lorena; Beumer, Wouter; Colasse, Sabrina; Drexhage, Hemmo; Versnel, Marjan; Bessis, Alain
Abstract Microglia colonise the brain parenchyma at early stages of development and accumulate in specific regions where they participate in cell death, angiogenesis, neurogenesis and synapse elimination. A recurring feature of embryonic microglial is their association with developing axon tracts, which, together with in vitro data, supports the idea of a physiological role for microglia in neurite development. Yet the demonstration of this role of microglia is lacking. Here, we have studied the consequences of microglial dysfunction on the formation of the corpus callosum, the largest commissure of the mammalian brain, which shows consistent microglial accumulation during development. We studied two models of microglial dysfunction: the loss‐of‐function of DAP12, a key microglial‐specific signalling molecule, and a model of maternal inflammation by peritoneal injection of lipopolysaccharide at embryonic day (E)15.5. We also took advantage of the Pu.1−/− mouse line, which is devoid of microglia. We performed transcriptional profiling of maternally inflamed and Dap12‐mutant microglia at E17.5. The two treatments principally down‐regulated genes involved in nervous system development and function, particularly in neurite formation. We then analysed the developmental consequences of these microglial dysfunctions on the formation of the corpus callosum. We show that all three models of altered microglial activity resulted in the defasciculation of dorsal callosal axons. Our study demonstrates that microglia display a neurite‐development‐promoting function and are genuine actors of corpus callosum development. It further shows that microglial activation impinges on this function, thereby revealing that prenatal inflammation impairs neuronal development through a loss of trophic support.